Examining cyber security implementation through TLS/SSL on academic institutional repository in Indonesia - Irhamni Ali (Berkala Ilmu Perpustakaan dan Informasi, 2021)
Introduction. This paper examines the cybersecurity of AIR in Indonesia by analyzing the security aspect focusing on the security protocols involving network called TLS (Transport Layer Security) and SSL (Secure Socket Layer), which has functions to secure the communication. Data Collection Methods. This research was conducted through experimental on the best AIR in Indonesia at private and public universities. Data Analysis. The data were descriptively analysed using scoring method of SSL Scoring. Results and Discussion. Several issues found was most Indonesian Academic Institutional Repositories have vulnerable security issues in their TLS/SSL and could cause problems disastrous for their information asset's security. Conclusion. Based on the findings, Indonesian AIR is urgent to implement security intervention for AIR to update the technology and policy to protect the information asset.